EFFECTS OF CORPORATE INCOME TAX ON THE PROFITABILITY OF MINING COMPANIES: EVIDENCE FROM GHANA STOCK EXCHANGE - Kumi, John Adu; Amaniampong, Martin; Kumi, Mary Adu (IJRDO - Journal of Business Management, 2018)
The tax rate of the mining sector in Ghana is viewed to be too high and has adverse effects on the profitability of mining firms in the country. There has been an outcry for the government to find ways to help curb this problem as mining companies in the country might become uncompetitive or even fold up if not checked. This study investigates the impact that corporate income tax has on profitability of mining companies in Ghana using ten years data from the year 2005 to 2014 with a sample of the only two listed mining firms on the Stock Exchange as at the time of the study. Return on assets was used as proxy for profitability as against corporate income tax which is the independent variable whereas company size, liquidity, leverage and growth were considered as control variables. The regression results showed that corporate income tax negatively influences profitability; whereas company size positively associates with profitability and liquidity, leverage and growth negatively impacted profitability. It was therefore recommended that government introduces the sliding scale method of taxation in the mining sector in order to make mining firms remain profitable whiles minor mining firms seek to increase their size of operations to be more competitive and profitable.